2009
DOI: 10.1111/j.1600-0625.2009.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

A guide to hair follicle analysis by transmission electron microscopy: technique and practice

Abstract: Hair follicles contain several tissues and cell types that differentiate down distinct pathways to provide for growth, keratinization and the maintenance of the hair shaft. Electron microscopy is useful for examining the morphological characteristics of developing hair follicles, including special types of keratinization, the timing of keratinization, programmed cell death, cell adhesion and separation, cell movement and changes in organelles. Hair follicles are one of the more challenging targets for electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(61 citation statements)
references
References 34 publications
4
51
0
6
Order By: Relevance
“…Many other KAPs as well as other type I and II hair keratins are expressed primarily in the mid-to upper cortex during the advanced stage of differentiation . TEM studies of follicles have revealed the appearance of hair keratin IF bundles, i.e., proto-macrofibrils (proto-MFs), in the lower cortex (Jones and Pope, 1985;Marshall et al, 1991;Morioka, 2009;Orwin, 1979;Orwin and Woods, 1982). Small proto-MFs reported to date are around 80 nm wide and 300-700 nm long (Marshall et al, 1991;Orwin, 1979), so they are similar in size to the short IF bundles formed by the combination of K35-K85 in this study (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Many other KAPs as well as other type I and II hair keratins are expressed primarily in the mid-to upper cortex during the advanced stage of differentiation . TEM studies of follicles have revealed the appearance of hair keratin IF bundles, i.e., proto-macrofibrils (proto-MFs), in the lower cortex (Jones and Pope, 1985;Marshall et al, 1991;Morioka, 2009;Orwin, 1979;Orwin and Woods, 1982). Small proto-MFs reported to date are around 80 nm wide and 300-700 nm long (Marshall et al, 1991;Orwin, 1979), so they are similar in size to the short IF bundles formed by the combination of K35-K85 in this study (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…MFs are the hair keratin IF bundles that are observed in the cortex of hair fibers and wool by transmission electron microscopy (TEM), and have maximum lengths of approximately 10 μm (Bryson et al, 2009;Chapman and Gemmell, 1971;Jones and Pope, 1985;Marshall et al, 1991;Morioka, 2009;Orwin, 1979;Orwin and Woods, 1982;Plowman et al, 2007). In MFs, hair keratin IFs are embedded in a matrix material composed of hair keratinassociated proteins (KAPs) that link each other and to IFs .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the interface between the Cuh and the inner root sheath cuticle (Cui) form an interlocking structure to anchor the developing hair shaft in the base of the hair follicle, which can be seen from an electron-dense aggregate structures in the outermost layer of the WT Cuh (Fig. 3 E and F) (16). This electron-dense structure is likely to be aggregated keratin filaments as it was found to show positive immunoreactivity to K82 and K32 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is accompanied by multiple biological processes such as a specific expression of different keratins and keratin-associated proteins (KAPs) (19) that lead, together with the reorganization of the keratin network and the loss of water, to a compaction and hardening of the fiber. However, although several complementary studies analyzed the changes in the network architecture accompanying the keratinization process (20)(21)(22), little is known about the consequence, its mechanical hardening.…”
mentioning
confidence: 99%